(untitled) (PERcursos Linguísticos, 2025)
The main objective of this article is to discuss how the Portuguese language teacher can improve his didactic strategies in the literacy of students belonging to the elderly who seek to learn to read in that language. In this article, we seek to intersect theoretical aspects of Applied Linguistics, such as teaching the mother tongue and the transdisciplinarity of this area of ​​knowledge, interconnecting them with Literacy Studies in a sociocultural perspective with regard to the literacy and schooling of the elderly. The methodology of this research report is a qualitative bibliographic with regard to data analysis, collected through investigations in materials already published, in particular, scientific articles, dissertations and theses, in addition to others that served as the basis for the discussions.